1998
DOI: 10.1046/j.1365-294x.1998.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the endangered Pampas deer (Ozotoceros bezoarticus)

Abstract: The Pampas deer (Ozotoceros bezoarticus L. 1758) is the most endangered neotropical cervid, and in the past occupied a wide range of open habitats including grassland, pampas, savanna, and cerrado (Brazil) from 5 degrees to 41 degrees S. To better understand the effect of habitat fragmentation on gene flow and genetic variation, and to uncover genetic units for conservation, we examined DNA sequences from the mitochondrial control region of 54 individuals from six localities distributed throughout the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 31 publications
4
53
2
4
Order By: Relevance
“…These results are quite distinct from those obtained by González et al (1998) for mtDNA. This can be a consequence of the differences in the genetic characteristics of the markers used in each study, since different classes of markers can give rise to very distinct results.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…These results are quite distinct from those obtained by González et al (1998) for mtDNA. This can be a consequence of the differences in the genetic characteristics of the markers used in each study, since different classes of markers can give rise to very distinct results.…”
Section: Discussioncontrasting
confidence: 98%
“…These results are concordant with González et al (1998) that found a remarkably high variability in the control region of the mitochondrial DNA. This high genetic variability at nuclear (RAPD) and mtDNA at both populations can reflect the historically large population sizes and their recent decline.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations